2019
DOI: 10.3390/ani9040139
|View full text |Cite
|
Sign up to set email alerts
|

Rearing Undocked Pigs on Fully Slatted Floors Using Multiple Types and Variations of Enrichment

Abstract: In fully slatted systems, tail biting is difficult to manage when pigs’ tails are not docked because loose enrichment material can obstruct slurry systems. This pilot study sought to determine: a) whether intact-tailed pigs can be reared with a manageable level of tail biting by using multiple slat-compatible enrichment; b) whether a variation of enrichment has an effect; and c) whether pigs show a preference in enrichment use. Ninety-six undocked pigs were given the same enrichment items from one week after b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 38 publications
2
35
1
4
Order By: Relevance
“…Despite the numerous tail biting outbreaks recorded, overall tail lesion scores in the current experiment were lower than expected. In fact they were lower than those recorded in another study with undocked pigs, which recorded no tail biting outbreak [ 36 ]. The low tail lesion scores are likely due to the timing of the scoring: pigs were scored every 2 weeks, and based on the experimenter’s experience, tail lesions tend to heal quickly.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Despite the numerous tail biting outbreaks recorded, overall tail lesion scores in the current experiment were lower than expected. In fact they were lower than those recorded in another study with undocked pigs, which recorded no tail biting outbreak [ 36 ]. The low tail lesion scores are likely due to the timing of the scoring: pigs were scored every 2 weeks, and based on the experimenter’s experience, tail lesions tend to heal quickly.…”
Section: Discussioncontrasting
confidence: 67%
“…Nevertheless, the overall impact of tail biting in this study was severe, and the effectiveness of either of these single-point enrichment items was marginal. To our knowledge, no study to date has yet demonstrated the possibility of managing tail biting in undocked pigs without loose rooting materials provided on the floor or via dispensers [ 36 ]. Frustration from the inability to satisfy the natural motivation to explore and forage due to inadequate materials is a major cause of tail biting in pigs [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These were selected so that they were appropriate to the pigs' age in the weaner and finisher stages. In a previous study (13), a variety of enrichment materials were used for undocked pigs housed on fully slatted floors, and resulted in no tail biting outbreaks, and low levels of tail damage. The most used and sustainable materials in that study (13) were chosen for this study.…”
Section: Experimental Designmentioning
confidence: 99%
“…Provision of loose bedding materials such as straw satisfies these criteria and is considered effective in reducing tail biting (7)(8)(9), but on fully slatted floors straw can block slurry removal systems (10). Many studies have investigated alternative ways of supplying loose materials that are compatible with slatted floors: in elevated fittings (11)(12)(13)(14)(15)(16), as a compressed form in solid blocks (16,17), or in floor feeders (18). However, simply providing loose materials in a fixed location for pigs to interact with has not been as effective in reducing tail biting in undocked pigs as provision of material on the pen floor (14,18); what is more effective when managing tail biting in undocked pigs, is combining the provision of loose materials in a smaller quantity with other point-source enrichment items (13,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation